Magnetic Resonance Appearance of Gastric-Type Adenocarcinoma of the Uterine Cervix in Comparison With That of Usual-Type Endocervical Adenocarcinoma: A Pitfall of Newly Described Unusual Subtype of Endocervical Adenocarcinoma. Issue 8 (1st October 2014) - Kido, Aki; Mikami, Yoshiki; Koyama, Takashi; Kataoka, Masako; Shitano, Fuki; Konishi, Ikuo; Togashi, Kaori
Abstract : Objective: The aim of this study was to evaluate the characteristics of gastric-type adenocarcinoma (GAS) of the uterine cervix, compared with usual-type endocervical adenocarcinoma (UEA) and squamous cell carcinoma (SCC), using magnetic resonance (MR) imaging. Materials and Methods: A total of 15 histopathologically defined GASs, 12 UEAs, and 40 SCCs were retrieved from archive files and were included for evaluation. Microscopic features, as well as topography and tumor growth pattern, and presence or absence of coexistence of cystic cavities were evaluated. Accuracy of evaluation for parametrial tissue and vaginal wall invasion was also evaluated by 2 diagnostic radiologists, independently, without clinical information on cases. Results: Thirteen (86.70%) of the 15 cases of GAS exhibited tumors in the higher portion of cervical canal or the entire cervix. On the other hand, SCCs and UEAs were mainly located in the lower portion of cervical canal, at a frequency of 21 of 40 (52.5%) and 9 of 12 (75.0%), respectively. Involvement of the corpus was observed more frequently in cases of GAS with an occurrence of 8 of 15 (53.3%), whereas in all cases of UEA and in 5 of the 40 cases of SCC, the corpus was free of tumor. In GAS cases, the predominant pattern of growth was highly infiltrating and endophytic (14/15, 93.3%), whereas an exophytic growth pattern was observed in 31 (77.5%) of the 40 SCC cases and 11 (91.7%) of the 12 UEA cases. Cystic cavities associated with tumors were identified in only 1 case of SCC but occurred in 12 (80.0%) of the 15 GASs and 4 (33.3%) of the 12 UEAs. Diagnostic accuracies of more than 70% and more than 60% were reached in parametrial invasion and vaginal invasion, respectively, in GAS. Conclusion: Distinctive MR imaging features of GAS were infiltrating mass of endophytic growth, location in the upper cervical canal, and association with tiny cysts. This characteristic appearance can be a clue for the evaluation of extent of tumor based on MR imaging.